Implementasi Kebijakan Pajak Daerah Di Kota Palembang - Elviany, Feby Hestri; Hakim, Arif Rahman; Hestirinaih, Deby Chintia (@-Publik: Jurnal Administrasi Publik, 2025)
This research is descriptive research with a qualitative approach. The data used is based on type, namely quantitative data and qualitative data, while based on primary data sources and secondary data. Observations, interviews and documentation were used as data collection tools. The informants in this research were the Head of Other Regional Taxes, BPPD Palembang City; Head of Regional Tax Receivables Management Division BPPD Palembang City; Head of Regional Tax Assessment & Development Division BPPD Palembang City; Head of PBB & BPHTB BPPD Palembang City; Other related parties, Police / Kodim / Prosecutor's Office; People/taxpayers (individuals/business entities) who are tax compliant and tax non-compliant in Palembang City. The data analysis used is qualitative analysis with an interactive model. Based on the research results, it is concluded that the implementation of Regional Tax Policy in the City of Palembang has been implemented although it is not yet optimal.